Industry 4.0 – The Global Industrial Revolution: Achievements, Obstacles and Research Needs for the Digital Transformation of Industry - Johannes Winter (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Special Issue delves into the strides made, challenges encountered, and research imperatives within the realm of Industrie 4.0 from both a scientific and practical standpoint. This publication features the voices of Industrie 4.0 pioneers Henning Kagermann and Wolfgang Wahlster, as well as leaders in research and industrial application of smart manufacturing concepts.
Keywords: 330; Industrie 4.0; intelligent manufacturing; smart factories; industrial artificial intelligence; digital twins; zero-defect manufacturing; digital ecosystems; China Manufacturing 2025; Industrial Internet; Cloud Manufacturing; digitalization; small-medium enterprises; new business models; data democratization